IMPLEMENTASI PENGEMBANGAN EKOWISATA BERBASIS MASYARAKAT DI HUTAN LINDUNG GUNUNG SIRIMAU KOTA AMBON - Mersiana Sahureka; H. Lelloltery; J. Ch. Hitipeuw (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2016)
Longterm goals to be achieved from this study was to determine the benefitts of ecotourism activities for the improvement of public welfare and conservation of natural resources in the protected forests of Mount Sirimau. Specific targets to be achieved is to know the tourism development strategy by focusing on real public participation through community participation in the entire ecotourism activities ranging from planning to evaluation monitoring.Metode research used survey method by observation, interviews and focus group discussions between groups of conscious travel, community and government Hukurila country. FGD conducted modified from the PRA method with the process includes the formulation of the problem, identification of alternative problem-solving and implementation. Cooperation with stakeholders through a partnership approach. Data were analyzed qualitative descriptive to describe implimentasi community-based ecotourism development. The results showed that the group of tourism awareness â€œNineâ€ into institutional forum in the village who managed Hukurila ecotourism in the country. Activities include participatory community activities in terms of return decisions, participation in the implementation of activities such as a tour guide providers, providers of food and beverage services, environmental cleanup and promotion of tourist sites and providers of travel and participation and maintenance of facilities and infrastructure. While the partnership approach includes the development of local human resources such as training Website creatio cooperation aware group travel with community organizations, counseling with the theme â€œPrecious Hukurilaâ€ about the introduction of the surrounding environment. Cooperation Foundation Heka Leka, YES (Youth Exchanges and Study USA).